Des méthodes quantitatives appliquées au secteur des exportations québécoises, 1969 - Nappi, Carmine (L'Actualité économique)

(untitled) (HEC Montréal, 1974)
AbstractThis paper explores the relationship between the structural models and different trade indices which can be used to quantify Quebec and other Canadian regions export sector. An attempt is made to measure the degrees of specialization of exports for fifty goods, the interprovincial and international export intensity indices for the five Canadian regions, and the export performance indices for the provinces under study. The conclusion highlights the importance of the east-west Canadian trade, specially for the internal provinces. Finally, the Quebec commercial characteristics in relation with those of other Canadian provinces (and the need to take them into account when formulating a federal trade policy) are outlined and stressed.